Ultra-low-dose CT-guided lung biopsy in clinic: radiation dose, accuracy, image quality, and complication rate. (February 2021) - Liang, Ting; Du, Yonghao; Guo, Chenguang; Wang, Yuan; Shang, Jin; Yang, Jian; Niu, Gang
Background: Computed tomography (CT)-guided percutaneous lung biopsy is usually performed by helical scanning. However, there are no studies on radiation dose, diagnostic accuracy, image quality, and complications based on axial scan mode. Purpose: To determine radiation dose, accuracy, image quality, and complication rate following an ultra-low-dose (ULD) protocol for CT-guided lung biopsy in clinic. Material and Methods: A total of 105 patients were enrolled to receive CT-guided lung biopsy. The use of an ULD protocol (axial scan) for CT-guided biopsy was initiated. Patients were randomly assigned to axial mode (Group A) and conventional helical mode (Group B) CT groups. 64-slice CT was performed for CT-guided pulmonary biopsy with an 18-G coaxial cutting biopsy needle. The radiation dose, accuracy, image quality, and complication rate were measured. Results: Ninety-seven patients were selected for the final phase of the study. There was no significant difference between the two groups for pulmonary nodule characteristics ( P  > 0.05). The mean effective dose in group A (0.077 ± 0.010 mSv) was significantly reduced relative to group B (0.653 ± 0.177 mSv, P < 0.001). There was no significant difference in accuracy, image quality, and complication rate ( P  > 0.050) between the two modes. Conclusion: An ULD protocol for CT-guided lung nodule biopsy yields a reduction in the radiation dose without significant change in the accuracy, image quality, and complication rate relative to the conventional helical mode scan.